MAKNA ETIKA SEBAGAI LANDASAN MENTAL SPIRITUAL PENDIDIK YANG PROFESIONAL DI ZAMAN MILENIAL - I Made Putra Aryana (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2020)
This article describes educators in applying ethics as spiritual mental foundations in the millennial period. Discussing the importance of ethics as the mental and Spiritual foundation of Hindu educators to control emotions and behaviours in carrying out the duties of education and teaching in the millennial age. Discussed using observation methods, literature studies and interviews. The attitude of a professional educator, which is avoiding the prohibition of Hindu religion that can inhibit the development of professional and student development. Based on the analysis, a profesioteenic education in the millennial period is obliged to uphold ethics as the foundation of its spiritual spirituality. The Foundation has Hindu teachings, such as Panca Sraddha, Catur Purusa Artha, Trikaya Parisudha, Dharma Laksana.